IDENTIFIKASI FAKTOR-FAKTOR RISIKO PADA PROYEK INFRASTRUKTUR DASAR DAN FASILITAS UMUM PENUNJANG PARIWISATA DI PELABUHAN BENOA, BALI - I Komang Agus Ariana; I Gusti Ngurah Putu Dharmayasa; I Nengah Riana; Nyoman Bayu Kurniawan Bendesa (PADURAKSA: Jurnal Teknik Sipil Universitas Warmadewa, 2023)
In general, risks in construction projects can affect project objectives, namely affecting costs, quality and time. In a construction project, a risk factor is a possibility that causes a loss. This study was conducted to determine the dominant risk factors and risk mitigation that caused delays in the implementation of the basic infrastructure and tourism support public facilities project at Benoa Harbor. In this study, data was collected through a questionnaire which was then checked for validity, correlation and reliability using SPSS. Furthermore, to determine the dominant risk, the Severity Index method is used. Based on this research, there are 20 risk factors that cause project delays. The dominant risks based on the level of risk are unexpected events (natural disasters, fires) of 12%, changes in work that has been completed by 10%, environmental changes including changes in weather or climate. at project sites by 10%, repairs that are not in accordance with specifications by 8%, and limited authority of personnel/owners in making decisions by 8%. The dominant risks identified in the project really need to find solutions because they have a very significant impact on project performance.